Correlation between adolescent orthodontic quality of life and ABO Discrepancy Index in an orthodontic treatment-seeking population: A cross-sectional study. (December 2021) - Swan, Matthew; Tabbaa, Sawsan; Buschang, Peter; Toubouti, Youssef; Bashir, Rehana
Objective: To evaluate the association between adolescents' orthodontic quality of life before initiating orthodontic treatment and their objective case complexity as measured by the American Board of Orthodontics' Discrepancy Index (DI). Design and setting: A single-centre, cross-sectional survey study. Methods: The Orthodontic Quality of Life Assessment Survey (OQoLAS) was administered to 240 adolescents (aged 11–14 years) during their record-gathering appointment. After completion of the survey, a DI score was calculated for each patient based on pretreatment measurements. Pearson correlation coefficients, r, were used to assess the association of DI scores with OQoLAS total and subdomain scores. A multiple linear regression of OQoLAS total scores adjusting for age, gender and DI scores was conducted. Results: The study did not find a strong correlation between OQoLAS and DI scores (r = 0.10; P = 0.6497). On average, the OQoLAS scores (functional, emotional and social subdomains of OQoLAS) were slightly higher among girls than among boys but there was no statistical difference for total OQoLAS score between boys and girls (42.4 vs. 45.4, P = 0.2005). However, there was a significant difference in oral health perception rating between boys and girls, with girls being more likely to rate their oral health positively (adjusted P = 0.0226). The total DI scores of boys with respect to girls were not statistically different ( P = 0.4256). The components of the DI that showed highest score were for cephalometric measures, followed by overjet; and the lowest scores were for lateral open bite and buccal posterior crossbite. The measure of association analysis did not show any strong correlation between the OQoLAS (total score and subdomain scores), and DI score or any of its components. Conclusion: Malocclusion severity was not found to be correlated with orthodontic quality of life in adolescents aged 11–14 years seeking orthodontic treatment.